1982
DOI: 10.1002/j.1460-2075.1982.tb01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of malT, the regulator gene of the maltose region in Escherichia coli, is limited both at transcription and translation.

Abstract: Six mutations, which lead to an increase in malT expression, were mapped by sequencing techniques. All of them had one or other of two base changes. Determination of the transcription start point by reverse transcriptase mapping localised the two base changes with respect to the elements that control malT expression. One of the base changes (malTp1) is located in the Pribnow box of the promoter, and presumably results in an increase in the rate of transcription initiation. The other (malTp7) is located in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 25 publications
3
64
0
Order By: Relevance
“…Translational noise control is a means by which genetic circuits can reduce noise in such cascades. Regulatory genes such as the cI gene of phage (2) and the malT gene of Escherichia coli (19) are often poorly translated. It has been pointed out by other researchers (e.g., ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translational noise control is a means by which genetic circuits can reduce noise in such cascades. Regulatory genes such as the cI gene of phage (2) and the malT gene of Escherichia coli (19) are often poorly translated. It has been pointed out by other researchers (e.g., ref.…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out by other researchers (e.g., ref. 19) that this translational inefficiency might be sustained in the genome through the resulting beneficial reduction in noise. However, we note that in some situations, the intrinsic noise of a regulator can actually increase the sensitivity with which its signal is transmitted (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The maltose system is subjected to catabolite repression as well as inducer exclusion. Thus, the expression of malT as well as some of the MalT-dependent genes (i.e., the ones encoding transport proteins) is controlled by the cyclic AMP/catabolite gene activator protein system (10), which in turn is controlled by the PtsG-mediated transport of glucose (46). EIIA Glc -mediated catabolite repression on malT is also exerted by growth on glycerol, most likely affecting the EIIA Glc -P-dependent stimulation of adenylate cyclase by glycerol-3-P (19,20).…”
mentioning
confidence: 99%
“…In the absence of inducer, both transcription and translation of malT are limited to a low level because of its poor promoter and the unfavorable ribosome binding site (6). It has been demonstrated that CAP stimulates malT expression by promoting the binding of RNA polymerase to the rather poor promoter (8).…”
Section: Vol 179 1997mentioning
confidence: 99%